2015
DOI: 10.4038/tar.v26i1.8068
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing motivation to transfer training: an empirical study of a government sector training program in Sri Lanka

Abstract: Research related to factors affecting transfer of training in the government sector in Sri Lanka is extremely limited. Hence, this article examines the impact of two trainee characteristics (self efficacy and career commitment) and four work environmental factors (supervisory support, opportunity to perform, awareness of strategic linkages and accountability) on motivation to transfer. Data were collected from 152 officers of the Sri Lanka Administrative Service who participated in a capacity building training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…Some research studies have found a positive relationship between supervisors’ support and the motivation to transfer training (e.g., Brinkerhoff & Montesino, 1995; Chiaburu, Van Dam, & Hutchins, 2010; Clark, Dobbins, & Ladd, 1993; Cohen, 1990; Facteau et al, 1995; Gregoire, Propp, & Poertner, 1998). Other researchers have not found any relationship between supervisory support and the transfer of training (Madagamage et al, 2014; Russell, Terborg, & Powers, 1985; van der Klink, Gielen, & Nauta, 2001). Noe and Schmitt (1986) identified support from the supervisor as an important factor for the transfer of training in an organization.…”
Section: Literature Reviewmentioning
confidence: 82%
See 2 more Smart Citations
“…Some research studies have found a positive relationship between supervisors’ support and the motivation to transfer training (e.g., Brinkerhoff & Montesino, 1995; Chiaburu, Van Dam, & Hutchins, 2010; Clark, Dobbins, & Ladd, 1993; Cohen, 1990; Facteau et al, 1995; Gregoire, Propp, & Poertner, 1998). Other researchers have not found any relationship between supervisory support and the transfer of training (Madagamage et al, 2014; Russell, Terborg, & Powers, 1985; van der Klink, Gielen, & Nauta, 2001). Noe and Schmitt (1986) identified support from the supervisor as an important factor for the transfer of training in an organization.…”
Section: Literature Reviewmentioning
confidence: 82%
“…The capability and motivation of the trainees are equally important to determining training performance. The influence of employee self-efficacy on motivation to transfer training is found to be significant in Saudi Arabia (Al-Eisa et al, 2009) and Sri Lanka (Madagamage et al, 2014). Based on these findings, the following hypothesis has been developed in this study.…”
Section: Self-efficacy and Motivation To Transfermentioning
confidence: 90%
See 1 more Smart Citation
“…This includes peer support and supervisor support. Madagamage, Warnakulasooriya, and Wickramasuriya (2014) explain that "supervisory support to the trainees takes different forms, such as encouraging participation in training, assisting to apply by changing the work environment, providing feedback, and reinforcing positively" (p. 4). Russ-Eft (2002) in her earlier work focused on the situational elements that directly affect the trainee and expanded her typology to include supervisor and peer support or sanction; workload; and opportunity to use.…”
Section: Support and Organizational Environment That Affect Training mentioning
confidence: 99%
“…Further, the effectiveness of training can also be influenced by the attitude, expectations, values and interests of individuals. Individual characteristics would also include traits such as cognitive ability, conscientiousness, self-efficacy, anxiety, motivation and achievement (Madagamage et al, 2014). Since it is difficult to consolidate all these personal traits for the strategic training, the organization choses the individual characteristic suitable for their firm.…”
Section: Personal Characteristicsmentioning
confidence: 99%